Modifikasi Oil Breather System Dengan Selang High Temperature Pada Yamaha MIO-J Tahun 2012 - Askan; Muhammad Fakhrurozi (FT- UNDAR, 2018)
Motorized vehicles are one of the most widely used means of transportation in everyday life by the community. Engine performance is supported by the presence of an engine that complements the vehicle's performance due to the engine as a lubricant in motorized vehicles. In motorized vehicles, it is often found that engine problems are quickly hot when used by drivers when traveling long distances and even when stuck in traffic. To overcome this problem, an Oil Breather System will be added to the vehicle by punching a hole on the right side of the engine and planting a nipple for the hose holder Oil Breather System. From that point on, the oil will flow quickly directly from the oil pump. The oil is then passed on the hose to the Oil Breather System. From there the oil is cooled by gusts of wind received by the Oil Breather System and proceed to the Oil Breather System hole. Therefore, the Oil Breather System was installed in motorized vehicles. With the installation of the Oil Breather System in the Cover Valve section, the Cover driven chain air heat temperature on the 2012 Yamaha Mio-J vehicle engine can be reduced by a temperature of 5 ° C. This research will continue for other types of vehicles.